Longitudinal stability of molecular alterations and drug response profiles in tumor spheroid cell lines enables reproducible analyses - A.C. Nickel (Elsevier, 2021)
The utility of patient-derived tumor cell lines as experimental models for glioblastoma has been challenged by limited representation of the in vivo tumor biology and low clinical translatability. Here, we report on longitudinal epigenetic and transcriptional profiling of seven glioblastoma spheroid cell line models cultured over an extended period. Molecular profiles were associated with drug response data obtained for 231 clinically used drugs. We show that the glioblastoma spheroid models remained molecularly stable and displayed reproducible drug responses over prolonged culture times of 30 in vitro passages. Integration of gene expression and drug response data identified predictive gene signatures linked to sensitivity to specific drugs, indicating the potential of gene expression-based prediction of glioblastoma therapy response. Our data thus empowers glioblastoma spheroid disease modeling as a useful preclinical assay that may uncover novel therapeutic vulnerabilities and associated molecular alterations.